Altered vulnerability to asthma at various levels of ambient Benzo[a]Pyrene by CTLA4, STAT4 and CYP2E1 polymorphisms - Choi, Hyunok; Tabashidze, Nana; Rossner, Pavel; Dostal, Miroslav; Pastorkova, Anna; Kong, Sek Won; Gmuender, Hans; Sram, Radim J (Environmental pollution (Barking, Essex, 2017)
BACKGROUND: Within fossil- and solid-fuel dependent geographic locations, mechanisms of air pollution-induced asthma remains unknown. In particular, sources of greater genetic susceptibility to airborne carcinogen, namely, benzo[a]pyrene (B[a]P) has never been investigated beyond that of a few well known genes. OBJECTIVES: To deepen our understanding on how the genotypic variations within the candidate genes contribute to the variability in the children's susceptibility to ambient B[a]P on doctor-diagnosed asthma. METHODS: Clinically confirmed asthmatic versus healthy control children (aged, 7-15) were enrolled from historically polluted and rural background regions in Czech Republic. Contemporaneous ambient B[a]P concentration was obtained from the routine monitoring network. The sputum DNA was genotyped for 95 genes. B[a]P interaction with SNPs was studied by two-stage, semi-agnostic screening of 621 SNPs. RESULTS: The median B[a]P within the highly polluted urban center was 8-times higher than that in the background region (7.8 vs. 1.1 ng/m3) during the period of investigation. Within the baseline model, which considered B[a]P exposure-only, the second tertile range was associated with a significantly reduced odds (aOR = 0.28) of asthma (95% CI, 0.16 to 0.50) compared to those at the lowest range. However, the highest range of B[a]P was associated with 3.18-times greater odds of the outcome (95% CI, 1.77 to 5.71). Within the gene-environment interaction models, joint occurrence of a high B[a]P exposure range and having a high-risk genotype at CTLA4 gene (rs11571316) was associated with 9-times greater odds (95% CI, 4.56-18.36) of the asthma diagnosis. Similarly, rs11571319 at CTLA4 and a high B[a]P exposure range was associated with a 8-times greater odds (95% CI, 3.95-14.27) of asthma diagnosis. Furthermore, having TG + GG genotypes on rs1031509 near STAT4 was associated with 5-times (95% CI, 3.03-8.55) greater odds of asthma diagnosis at the highest B[a]P range, compared to the odds at the reference range. Also CYP2E1 AT + TT genotypes (rs2070673) was associated with 5-times (95% CI, 3.1-8.8) greater odds of asthma diagnosis at the highest B[a]P exposure. CONCLUSIONS: The children, who jointly experience a high B[a]P exposure (6.3-8.5 ng/m3) as well as susceptible genotypes in CTLA4 (rs11571316 and rs11571319), STAT4 (rs1031509), and CYP2E1 (rs2070673), respectively, are associated with a significantly greater odds of having doctor-diagnosed asthma, compared to those with neither risk factors.
Keywords: Genetic Predisposition to Disease; Dose-Response Relationship, Drug; vztah mezi dávkou a účinkem léčiva; Air Pollution; genotyp; vystavení vlivu životního prostředí; jednonukleotidový polymorfismus; STAT4 Transcription Factor; Male; Genotype; Česká republika; mužské pohlaví; studie případů a kontrol; Gene-Environment Interaction; znečištění ovzduší; Environmental Exposure; Czech Republic; dítě; bronchiální astma; Benzo(a)pyrene; Child; venkovské obyvatelstvo; městské obyvatelstvo; ženské pohlaví; Asthma; Single nucleotide polymorphism; Humans; antigen CTLA-4; Gene-environment interaction; benzopyren; Polycyclic aromatic hydrocarbon; Rural Population; interakce genů a prostředí; transkripční faktor STAT4; genetická predispozice k nemoci; CTLA-4 Antigen; Female; Cytochrome P-450 CYP2E1; Urban Population; cytochrom P-450 CYP2E1; Air pollution; lidé; Case-Control Studies; Polymorphism, Single Nucleotide